2016
DOI: 10.1017/jfm.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

Weakly nonlinear stability analysis of subcritical electrohydrodynamic flow subject to strong unipolar injection

Abstract: We analyse in detail the weakly nonlinear stability of electrohydrodynamic (EHD) flow of insulating fluids subject to strong unipolar injection, with and without cross-flow. We first consider the hydrostatic electroconvetion induced by a Coulomb force confined between two infinite flat electrodes, taking into account the charge diffusion effect. The effects of various non-dimensionalized parameters are examined in order to depict in detail and to understand better the subcritical bifurcation of hydrostatic ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 55 publications
7
35
0
Order By: Relevance
“…In the space-charge-limited (SCL) injection ( C →), the flow stability depends on c T alone [77][78][79]. The effect of charge diffusion was investigated by Zhang et al by employing linear stability analysis on the EC problem with a Poiseuille flow [42], and by non-linear analysis using a multiscale method [47]. The authors found that the charge diffusion has a nonnegligible effect on c T , and the transient behavior depends on the Reynolds number ( Re ) [42,47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the space-charge-limited (SCL) injection ( C →), the flow stability depends on c T alone [77][78][79]. The effect of charge diffusion was investigated by Zhang et al by employing linear stability analysis on the EC problem with a Poiseuille flow [42], and by non-linear analysis using a multiscale method [47]. The authors found that the charge diffusion has a nonnegligible effect on c T , and the transient behavior depends on the Reynolds number ( Re ) [42,47].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of charge diffusion was investigated by Zhang et al by employing linear stability analysis on the EC problem with a Poiseuille flow [42], and by non-linear analysis using a multiscale method [47]. The authors found that the charge diffusion has a nonnegligible effect on c T , and the transient behavior depends on the Reynolds number ( Re ) [42,47]. Li et al performed linear analysis to study convective instabilities in EHD-Poiseuille flow and found that the ratio of the Coulomb force to the viscous force has an impact on the transition of transverse rolls from convective to absolute instability [80].…”
Section: Introductionmentioning
confidence: 99%
“…Governing equations yield four non-dimensional parameters that describe the system's state [12,[17][18][19][20][21].…”
Section: Non-dimensional Analysis and Solution For Hydrostatic Statementioning
confidence: 99%
“…where H is the distance between the electrodes (distance between the two infinite plates), 0  is the injected charge density at the anode, and 0   is the voltage difference applied to the electrodes. The physical interpretation of these parameters are as follows: M -ratio between hydrodynamic mobility and the ionic mobility; T -a ratio between electric force to the viscous force; C -charge injection level; and Fe -reciprocal of the charge diffusivity coefficient [12,17].…”
Section: Non-dimensional Analysis and Solution For Hydrostatic Statementioning
confidence: 99%
See 1 more Smart Citation